Pax indica: India and the world of the 21st century - "Tharoor, Shashi" (New Delhi, 2012)
Pax Indica: India and the World of the Twenty-First Century is a book written by Shashi Tharoor. The book talks about India's relationship with the foreign nations in recent times. It also proposes ideas on how to lead a constructive relationship with other nations. Written by a significant figure in Indian politics, the book gives a promising account on India's foreign policy. Pax Indica is a book that was written directly by a person who is in politics. According to Tharoor, Indian diplomacy is handled in a high-level, with a big roar. The book is divided in to eleven chapters and talks first about India's closest and most controversial neighbor-Pakistan. The author deals with Pakistan's hostility towards India for various reasons. The author then moves on to China, other Asian countries, the Arab nations, the US, European, Africa and Latin America. In the act of explaining India's foreign policy, Tharoor takes a look at India's international relationships in detail and the global responsibility of India. He also analyses about the functioning of Ministry of External Affairs and opinions of parliament and public on the shaping of policy. Adding to the above, the author also gives a strategic vision of India's future foreign policies, suggesting that India must travel from non-alignment to multi-alignment. His motive lies on moving India's good relationships with other countries to a profitable trade, giving opportunities to the country's growth. Pax Indica is a substantial book written on foreign policy of India. The edition is published in hardcover, on 12th December, 2012.
Keywords: India-Foreign policy